Anti-oppressive pedagogy as an opportunity for consciousness raising in the music therapy profession: A critical disability studies perspective. (May 2022) - Pickard, Beth
In pedagogic literature informed by critical disability studies, academia is widely cited as an ableist institution: the training ground for the professions of normalcy. Music therapy could readily be complicit in this normalising discourse with its potential to pathologise participants and to maintain a strict 'normative divide', between professionals it trains and participants who engage with its provision. Activists, advocates and disabled therapists have posed a welcome challenge to this positioning in recent publications, but the pedagogical dimensions of music therapy training in this area have received less attention. The emerging signature pedagogy of music therapy and its omissions will be considered, which may explain the need for an increased social justice focus in music therapy curricula. This article considers the potential of applying Kumashiro's typologies of anti-oppressive education in music therapy training: problematising existing pedagogies and critically reflecting upon the potential of a social justice informed curriculum. These approaches have the potential to reframe Otherness by acknowledging expertise in lived experience. Through introducing these frameworks for socially just, anti-oppressive pedagogies, this article invites consciousness raising in music therapy pedagogy through engagement with critical disability studies theory and philosophy.